Desain Pembelajaran Kolaboratif Abad 21 Berbasis Nilai Al-Qur’an Dan Kontribusinya Bagi Murid Introver - Al-Ayubi, Muhammad Shalehuddin; Muhammad Shalehuddin (Jurnal TEKNODIK, 2025)
21st-century collaborative learning is generally designed with the assumption that active verbal participation and open social interaction are indicators of learning success. This assumption has the potential to marginalize introverted students who have reflective tendencies, deep thinking, and need a psychologically safe space. This article aims to describe and analyze Quranic Collaborative Learning Innovation (QCLI) as a 21st-century collaborative learning model that is friendly to introverted students by integrating Qur'anic values ​​​​and principles of educational psychology. The study uses a qualitative approach through literature studies confirmed by observation, interviews, and focus group discussions. Data analysis was conducted using triangulation to maintain the validity of the findings. The results show that QCLI is built on five Qur'anic value syntax, namely tasyakkur, ta'āruf, ta'āwun, tafakkur, and tadzkiah, which form a reflective, inclusive, and humanistic collaborative learning. This model contributes to increasing meaningful participation, psychological comfort, and strengthening the character of introverted students in 21st-century learning